IOT-BASED VANAME SHRIMP WATER QUALITY MONITORING PROTOTYPE USING GOOGLE SPREADSHEET - Arifani , Nico Bagus; Wisaksono , Arief (Journal for Technology and Science, 2024)
General Background: Effective monitoring of water quality is crucial in shrimp farming, as poor conditions can lead to significant harvest failures. Specific Background: The integration of Internet of Things (IoT) technology provides a promising solution for continuous water quality assessment, enabling farmers to monitor conditions remotely. Knowledge Gap: Despite advancements in monitoring technologies, there is limited research on the practical implementation of IoT-based systems in aquaculture settings, particularly for Vannamei shrimp. Aims: This study aims to develop an IoT-based water quality monitoring tool using a combination of sensors and cloud-based data storage to enhance shrimp farming productivity. Results: The system incorporates DS18B20, pH, and conductivity sensors linked to an Arduino Uno and NodeMCU ESP8266, successfully transmitting data to Google Sheets. The TDS sensor, DS18B20 sensor, and robotic DF pH sensor demonstrated accuracies of 98.59%, 98.59%, and 94.89%, respectively, with standard deviations indicating good reliability. Novelty: The proposed system offers a user-friendly interface via Google Sheets, allowing real-time monitoring without geographical constraints, making it accessible for farmers. Implications: The findings underscore the potential of IoT technologies in aquaculture for optimizing water quality management, thereby maximizing shrimp production and minimizing economic losses due to harvest failures. This innovative approach could serve as a model for future research and application in sustainable aquaculture practices.